2021
DOI: 10.1002/cne.25133
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide expression in the box jellyfish Tripedalia cystophora—New insights into the complexity of a “simple” nervous system

Abstract: Box jellyfish have an elaborate visual system and perform advanced visually guided behaviors. However, the rhopalial nervous system (RNS), believed to be the main visual processing center, only has 1000 neurons in each of the four eye carrying rhopalia. We have examined the detailed structure of the RNS of the box jellyfish Tripedalia cystophora, using immunolabeling with antibodies raised against four putative neuropeptides (T. cystophora RFamide, VWamide, RAamide, and FRamide). In the RNS, T. cystophora RF-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The opsins investigated in this study were originally identified from transcriptomics of juvenile and adult medusae of T. cystophora (Nielsen et al, 2019). Specific antibodies against three of the recovered opsins were produced in rabbits (Genosphere, Paris, France) using the following three amino acid sequences from their c-terminus:…”
Section: Custom-made Antibodies Against Opsinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opsins investigated in this study were originally identified from transcriptomics of juvenile and adult medusae of T. cystophora (Nielsen et al, 2019). Specific antibodies against three of the recovered opsins were produced in rabbits (Genosphere, Paris, France) using the following three amino acid sequences from their c-terminus:…”
Section: Custom-made Antibodies Against Opsinsmentioning
confidence: 99%
“…In this study, we raised antibodies against the three unidentified opsins recently discovered in transcriptomic data from the Caribbean cubozoan, Tripedalia cystophora (Nielsen et al, 2019). We used these antibodies to examine expression not only in polyps and medusae of T. cystophora but also in the hydromedusa, in Sarsia tubulosa, and in the ocellus-carrying rhopalia of the scyphomedusae Aurelia aurita and Cassiopea xamachana.…”
Section: Introductionmentioning
confidence: 99%
“…The rhopalium is a tentacle-derived hollow structure bearing statocysts and photoreceptors and is found only in Acraspeda (Berrill,1949). Cubozoans also have a single nerve ring in the bell in cubozoans (Garm et al, 2006, Nielsen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The rhopalium contains two lens eyes, as well as two pairs of simpler pit eyes and a statocyst ( Nilsson et al, 2005 ). Anatomical studies in Tripedalia cystophora showed that the rhopalial nervous system contains over 1,000 neurons, which can be further divided into several morphologically different cell types, some defined by the expression of neuropeptides ( Nielsen et al, 2021 ). While architecture of the neural circuits remains still largely unknown it has been shown that Tripedalia cystophora use visual cues from the surrounding world to alter its swimming behavior and thereby navigates in mangrove areas by using terrestrial cues seen through the water surface ( Petie et al, 2011 ; Garm et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…While architecture of the neural circuits remains still largely unknown it has been shown that Tripedalia cystophora use visual cues from the surrounding world to alter its swimming behavior and thereby navigates in mangrove areas by using terrestrial cues seen through the water surface ( Petie et al, 2011 ; Garm et al, 2012 ). The example of the rhopalial nervous system of cubozoans shows that in certain cnidaria species the nervous system may have evolved structures that are much more complex than the widely assumed simple nerve net ( Petie et al, 2011 ; Garm et al, 2012 ; Nielsen et al, 2021 ). While one may argue that medusae have an overall more complex lifestyle since they are freely swimming, also the behavioral capacity of polyps may be more complicated than naively expected.…”
Section: Introductionmentioning
confidence: 99%